Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve for [tex]\( f^{\prime \prime \prime}(\pi) \)[/tex] given the function [tex]\( f(x) = 2 \sin x \cos x + \frac{1}{3} x^3 - x^2 \)[/tex], let's go through the differentiation process step-by-step.
Given:
[tex]\[ f(x) = 2 \sin x \cos x + \frac{1}{3} x^3 - x^2 \][/tex]
1. First Step: Simplify the Trigonometric Part
Using the double angle identity, [tex]\(2 \sin x \cos x = \sin(2x)\)[/tex], the function can be rewritten:
[tex]\[ f(x) = \sin(2x) + \frac{1}{3} x^3 - x^2 \][/tex]
2. First Derivative [tex]\( f'(x) \)[/tex]
Compute the first derivative:
[tex]\[ f'(x) = \frac{d}{dx}(\sin(2x)) + \frac{d}{dx}\left(\frac{1}{3} x^3\right) - \frac{d}{dx}(x^2) \][/tex]
Using the chain rule and basic differentiation rules:
[tex]\[ \frac{d}{dx}(\sin(2x)) = 2 \cos(2x) \][/tex]
[tex]\[ \frac{d}{dx}\left(\frac{1}{3} x^3\right) = x^2 \][/tex]
[tex]\[ \frac{d}{dx}(x^2) = 2x \][/tex]
So:
[tex]\[ f'(x) = 2 \cos(2x) + x^2 - 2x \][/tex]
3. Second Derivative [tex]\( f''(x) \)[/tex]
Compute the second derivative:
[tex]\[ f''(x) = \frac{d}{dx}(2 \cos(2x) + x^2 - 2x) \][/tex]
Using the chain rule and basic differentiation rules:
[tex]\[ \frac{d}{dx}(2 \cos(2x)) = -4 \sin(2x) \][/tex]
[tex]\[ \frac{d}{dx}(x^2) = 2x \][/tex]
[tex]\[ \frac{d}{dx}(-2x) = -2 \][/tex]
So:
[tex]\[ f''(x) = -4 \sin(2x) + 2x - 2 \][/tex]
4. Third Derivative [tex]\( f'''(x) \)[/tex]
Compute the third derivative:
[tex]\[ f'''(x) = \frac{d}{dx}(-4 \sin(2x) + 2x - 2) \][/tex]
Using the chain rule and basic differentiation rules:
[tex]\[ \frac{d}{dx}(-4 \sin(2x)) = -8 \cos(2x) \][/tex]
[tex]\[ \frac{d}{dx}(2x) = 2 \][/tex]
[tex]\[ \frac{d}{dx}(-2) = 0 \][/tex]
So:
[tex]\[ f'''(x) = -8 \cos(2x) + 2 \][/tex]
5. Evaluate at [tex]\( x = \pi \)[/tex]
Substitute [tex]\( x = \pi \)[/tex] into the third derivative:
[tex]\[ f'''(\pi) = -8 \cos(2\pi) + 2 \][/tex]
Recall that [tex]\( \cos(2\pi) = 1 \)[/tex]:
[tex]\[ f'''(\pi) = -8 \times 1 + 2 = -8 + 2 = -6 \][/tex]
So:
[tex]\[ f'''(\pi) = -6 \][/tex]
Hence, the correct value is:
[tex]\[ \boxed{-6} \][/tex]
Given:
[tex]\[ f(x) = 2 \sin x \cos x + \frac{1}{3} x^3 - x^2 \][/tex]
1. First Step: Simplify the Trigonometric Part
Using the double angle identity, [tex]\(2 \sin x \cos x = \sin(2x)\)[/tex], the function can be rewritten:
[tex]\[ f(x) = \sin(2x) + \frac{1}{3} x^3 - x^2 \][/tex]
2. First Derivative [tex]\( f'(x) \)[/tex]
Compute the first derivative:
[tex]\[ f'(x) = \frac{d}{dx}(\sin(2x)) + \frac{d}{dx}\left(\frac{1}{3} x^3\right) - \frac{d}{dx}(x^2) \][/tex]
Using the chain rule and basic differentiation rules:
[tex]\[ \frac{d}{dx}(\sin(2x)) = 2 \cos(2x) \][/tex]
[tex]\[ \frac{d}{dx}\left(\frac{1}{3} x^3\right) = x^2 \][/tex]
[tex]\[ \frac{d}{dx}(x^2) = 2x \][/tex]
So:
[tex]\[ f'(x) = 2 \cos(2x) + x^2 - 2x \][/tex]
3. Second Derivative [tex]\( f''(x) \)[/tex]
Compute the second derivative:
[tex]\[ f''(x) = \frac{d}{dx}(2 \cos(2x) + x^2 - 2x) \][/tex]
Using the chain rule and basic differentiation rules:
[tex]\[ \frac{d}{dx}(2 \cos(2x)) = -4 \sin(2x) \][/tex]
[tex]\[ \frac{d}{dx}(x^2) = 2x \][/tex]
[tex]\[ \frac{d}{dx}(-2x) = -2 \][/tex]
So:
[tex]\[ f''(x) = -4 \sin(2x) + 2x - 2 \][/tex]
4. Third Derivative [tex]\( f'''(x) \)[/tex]
Compute the third derivative:
[tex]\[ f'''(x) = \frac{d}{dx}(-4 \sin(2x) + 2x - 2) \][/tex]
Using the chain rule and basic differentiation rules:
[tex]\[ \frac{d}{dx}(-4 \sin(2x)) = -8 \cos(2x) \][/tex]
[tex]\[ \frac{d}{dx}(2x) = 2 \][/tex]
[tex]\[ \frac{d}{dx}(-2) = 0 \][/tex]
So:
[tex]\[ f'''(x) = -8 \cos(2x) + 2 \][/tex]
5. Evaluate at [tex]\( x = \pi \)[/tex]
Substitute [tex]\( x = \pi \)[/tex] into the third derivative:
[tex]\[ f'''(\pi) = -8 \cos(2\pi) + 2 \][/tex]
Recall that [tex]\( \cos(2\pi) = 1 \)[/tex]:
[tex]\[ f'''(\pi) = -8 \times 1 + 2 = -8 + 2 = -6 \][/tex]
So:
[tex]\[ f'''(\pi) = -6 \][/tex]
Hence, the correct value is:
[tex]\[ \boxed{-6} \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.